Boganmeldelser - Berning, Jesper; Thorsen, Thorkil; Kyvsgaard, Britta; Eckhoff, Torstein; Baun, Arne; Nielsen, Ruth; Justesen, Signe; Andreasen, Marie.Louise (Nordisk Tidsskrift for Kriminalvidenskab, 1988)
Book reviews